'A considerable portion of the defence of the Empire': Lisbon and victualling the royal navy during the French Revolutionary War, 1793–18021. Issue 237 (6th May 2014) - Robson, Martin
Abstract Based on an assessment of primary archive material, this article casts new light on the implementation of a contractor‐based victualling system to meet initial demands of the royal navy at Lisbon during 1793–6; and on the subsequent development of a more formal arrangement under an official representative of the victualling board, the agent victualler at Lisbon, to meet the needs of stationing the Mediterranean fleet there until its closure in 1802. It concludes that the victualling operations allowed the fleet to maintain an operational presence and had a strategic effect beyond protecting Portugal.